2019
DOI: 10.1055/s-0039-1684034
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Obesity are Risk Factors for Thirty-Day Readmissions Following Skull Base Surgery

Abstract: Background Thirty-day readmission has become a significant health care metric reflecting the quality of care and on the cost of service delivery. There is little data on the impact of complications following skull base surgery (SBS) on emergency readmission. Identifying modifiable risk factors for readmission may improve care and reduce cost. Design The study was designed as a single-center retrospective cohort study. Methods Records for a consecutive series of 165 patients who underwent op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…After accounting for these differences using multivariate regression, our study isolated several independent risk factors for readmission or complication following lumbar decompression. Similar to numerous other studies in the orthopedic literature, smoking was found to be an independent risk factor for surgical complication or hospital readmission 36–42 . While this does not represent an unexpected finding, it does provide further support to clinicians when counseling patients on the adverse impact of smoking in the setting of lumbar decompression surgery.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…After accounting for these differences using multivariate regression, our study isolated several independent risk factors for readmission or complication following lumbar decompression. Similar to numerous other studies in the orthopedic literature, smoking was found to be an independent risk factor for surgical complication or hospital readmission 36–42 . While this does not represent an unexpected finding, it does provide further support to clinicians when counseling patients on the adverse impact of smoking in the setting of lumbar decompression surgery.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to numerous other studies in the orthopedic literature, smoking was found to be an independent risk factor for surgical complication or hospital readmission. [36][37][38][39][40][41][42] While this does not represent an unexpected finding, it does provide further support to clinicians when counseling patients on the adverse impact of smoking in the setting of lumbar decompression surgery. Renal failure was also a significant predictor of hospital readmission or complication, consistent with prior studies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although they excluded patients with pituitary adenomas in their analyses, Makwana et al reported that in their patients who underwent both endoscopic and open skull base surgery, smoking was associated with 30day readmissions and complications and this effect was independent of the number of pack-years of smoking. 15 In another study of the 2016 and 2017 National Readmission Database, Shahrestani, et al…”
Section: Discussionmentioning
confidence: 99%
“…18 The post-protocol group also had a statistically higher percentage of smokers, which is a known risk factor for postoperative infections and readmission rates in the neurosurgical population. [19][20][21]…”
Section: Accepted Manuscriptmentioning
confidence: 99%